Exploring Religious Moderation and Rahmatan lil-‘Alamin Understanding among Prospective Professional Islamic Education Teachers - Ardiansyah, Ade Arip; Fitrah, Aditya; Bin Salman, Fahmi Mochammad (Indonesian Journal of Islamic Religious Education, 2025)
This study investigates the level of understanding of religious moderation and the concept of Rahmatan lil-‘Alamin among prospective professional Islamic Education (PAI) teachers enrolled in the Teacher Professional Education (PPG) Program of the Ministry of Religious Affairs. Employing a descriptive quantitative survey design, data were collected from 1,287 participants of the 2025 Batch 3 PPG PAI Program using a validated and reliable questionnaire covering dimensions of religious moderation national commitment, tolerance, anti-violence, and cultural accommodation and Rahmatan lil-‘Alamin values such as compassion, justice, and public benefit. Data were analyzed using descriptive statistics, Pearson’s correlation, and ANOVA through SPSS. The findings reveal that participants exhibit a high level of understanding of both constructs, with notable variations across gender and educational background. A strong positive correlation was found between the understanding of religious moderation and Rahmatan lil-‘Alamin (r > 0.70, p < 0.01), indicating that higher moderation literacy aligns with greater internalization of universal Islamic values. These results affirm the strategic role of the PPG program as a transformative platform for developing educators who embody inclusive, tolerant, and humanistic perspectives in Islamic education. The study contributes to the literature by integrating two theoretical frameworks religious moderation and Rahmatan lil-‘Alamin ethics into a single empirical model.